Assessing 'functionality' in school mathematics examinations: what does being human have to do with it? - Drake, Pat; Wake, Geoffrey; Noyes, Andrew (Taylor and Francis Group, 2012)
This article analyses aspects of the process of developing ‘functional’ assessments of mathematics at the end of compulsory schooling in England. A protocol that was developed for scrutinising assessment items is presented. This protocol includes an indicator of the ‘authenticity’ of each assessment item. The data are drawn from scrutiny of 589 assessment items from thirty-nine formal unseen examinations taken by students aged sixteen, and the article illustrates ways that mathematics is presented in different contexts in examinations. We suggest that currently the ‘human face’ of the questions may serve to disguise routine calculations, and we argue that in formal examinations connections between mathematics assessments situated in context and functional mathematics have yet to be established.